Improving bioaccessibility and physicochemical property of blue-grained wholemeal flour by steam explosion - Kong, Feng; Zeng, Qinghua; Li, Yue; Zhao, Yang; Guo, Xingfeng (Frontiers in Nutrition, 2022)
Whole grain contains many health promoting ingredients, but due to its poor bioaccessibility and processibility, it is not widely accepted by consumers. Steam explosion was exploited to modify the nutritional bioaccessibility and the physicochemical properties of wholemeal flour in this study. In vitro starch digestibility, in vitro protein digestibility of wholemeal flour and total flavonoids content, total phenolics content of digestive juice were used to evaluate the bioaccessibility and significant variation (p<0.05) was noted. Results showed that steam explosion enhanced the gastric protein digestibility ranged from 5.67% to 6.92% and the intestinal protein digestibility ranged from 16.77% to 49.12%. Steam-exploded wholemeal flour (0.5 MPa, 5 min) had the highest protein digestibility and rapidly digestible starch content. Compared with native flour, steam explosion (0.5 MPa, 5 min) contributed to 0.72-fold and 0.33-fold increment of total flavonoids content and total phenolics content in digestible juice. Chemical changes of wholemeal flour induced by steam explosion, caused the changes in the solvent retention capacity, rheological property of wholemeal flour, and altered the falling number (and liquefaction number). An increasing tendency to solid-like behavior and the gel strength of wholemeal flour was significantly enhanced by steam explosion at 0.5 MPa for 5 min, while the gluten was not weakened. This work indicated that steam-exploded wholemeal flour (0.5 MPa, 5 min) could serve as a potential ingredient with the noticeable bioaccessibility and physicochemical property in cereal products.